Antitrust guidelines and policy statements. - United States. Department of Justice ([Washington, District of Columbia] : US Department of Justice, 2011)
Antitrust guidelines and policy statements source provides guidance and policy issued by the Department of Justice related to antitrust matters.
Description based on source information screen, viewed April 7, 2020.
Keywords: Antitrust law -- United States; Electronic books